Job Outcomes in the Towns of South Sudan : Jobs, Recovery, and Peacebuilding in Urban South Sudan - Technical Report I - Finn, Arden; von der Goltz, Jan; Saidi, Mira; Sharma, Ambika (World Bank, Washington, DC, 2020)
This study assesses jobs outcomes in the towns of South Sudan, based on a 2017 household survey and a dedicated 2019 youth jobs survey. It discusses how years of conflict have touched nearly all livelihoods, leaving few productive jobs, and causing high poverty. Most urban households diversify their job activities little, and rely on household work in agriculture, commerce or personal services, or they depend on a household member’s work for NGOs or as a public servant. Many young workers say they are ready to build from the less than attractive job activities available. Workers point to a lack of funding, insecurity, and low demand as the main obstacles to doing better. The study is one of a set of four reports assessing different aspects of jobs in urban South Sudan in order to formulate policy for recovery.